The Role of Youth Entrepreneur and Employment Support Services (YESS) Program to Increasing Beneficiary Income: A Comparative Study of West Java and East Java - Harjanti, Miko; Astuti, Linda Tri Wira (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2025)
This study aims to analyze the role of the YESS Program in increasing the income of beneficiaries in two provinces, West Java and East Java, using panel data regression methods. The data used includes information related to the realization of Training,  realization of grants and subsidies, and Realization of Operating Expenses in both provinces. The results show that the income per beneficiary in West Java is lower compared to East Java. The average income per beneficiary in West Java is Rp 1,849,195/person and in East Java it is Rp2,124,039/person. In West Java, the most significant factor influencing the income of beneficiaries is the realization of grants and subsidies, indicating that the allocation of grants and subsidies has a substantial impact on income improvement. Meanwhile, in East Java, the most influential factor is the realization of program operations, suggesting that the success of program implementation is more decisive in increasing the income of beneficiaries in this region. This study provides insights into the effectiveness of the YESS Program, which can be influenced by local contexts and factors of implementation that differ between the two provinces. The implication of these findings is that policy interventions like YESS should go beyond technical training by also improving access to capital and providing ongoing mentoring. This integrated approach is more effective in boosting business performance and income for millennial farmers.